The Impact of Zoledronic Acid and Radioactive Iodine Therapy on Morbi-Mortality of Patients with Bone Metastases of Thyroid Cancer Derived from Follicular Cells. Issue 1 (3rd January 2019) - Andrade, Fernanda; Probstner, Danielle; Decnop, Marcus; Bulzico, Daniel; Momesso, Denise; Corbo, Rossana; Vaisman, Mario; Vaisman, Fernanda
Abstract : Objective: Bone metastases bring greater morbi-mortality to patients with differentiated thyroid carcinoma (DTC). Treatment was limited to radioactive iodine (RAI) and local approaches. Currently, bisphosphonates are included in the therapeutic arsenal. The aim of this study is to evaluate the impact of bone metastases and their treatment with zoledronic acid (ZA) and RAI therapy. Methods: We retrospectively review 50 DTC patients with structurally evident bone metastases followed in a tertiary cancer center from 1994 to 2018. Clinical-pathologic characteristics, skeletal related events (SRE), and therapeutic approaches were recorded. Results: Among the 50 patients analyzed, 22 underwent ZA adjuvant therapy and 28 did not. Mortality rate was 44%. Those patients presented SREs more frequently (90.9 vs. 67.9% the survival group, p = 0.05) and also had a greater number of bone lesions (40.9 vs. 10.7% had more than 6 metastatic sites, p = 0.03). The same group of patients was analyzed before and after therapy with ZA and the incidence of SRE decreased from 1.81 (0–8) before therapy to 0.29 (0–7) after therapy ( p = 0.006). Comparing similar groups of 22 patients treated with ZA with 28 patients not treated, there was a trend of better overall survival (OS) in the group that received this drug (147 vs. 119 months, p = 0.06) and significantly improvement when bone metastases were RAI avid 155 (125–185) versus 120 (85–157) months, p < 0.01. Conclusion : ZA can successfully diminish the chance of having new SRE and possibly affect OS in DTC patients with bone metastases. The positive impact of RAI adjuvant treatment on OS is directly associated with RAI uptake.